2011
DOI: 10.1093/carcin/bgr009
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin promotes CCL5-mesenchymal stromal cell-mediated breast cancer metastasis

Abstract: The interaction between cancer and its local microenvironment can determine properties of growth and metastasis. A critical component of the tumor microenvironment in this context is the cancer-associated fibroblast (CAF), which can promote tumor growth, angiogenesis and metastasis. It has been hypothesized that CAF may be derived from mesenchymal stromal cells (MSC), derived from local or distant sources. However, the signaling mechanisms by which tumors and MSCs interact to promote CAF-dependent cancer growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 24 publications
(30 reference statements)
7
128
0
6
Order By: Relevance
“…Previous studies by others have mostly focused on tumor-derived CCL5, and found overexpression of CCL5 in advanced stages of breast cancer [5]. In more recent years, mesenchymal stem cell-derived CCL5 has been shown to contribute to cancer cell motility, invasion and metastasis [49,50]. 4T1 growth characteristics parallel highly invasive human metastatic mammary carcinoma comparable with human stage IV breast cancer [51].…”
Section: Yan Zhang Et Al 405mentioning
confidence: 99%
“…Previous studies by others have mostly focused on tumor-derived CCL5, and found overexpression of CCL5 in advanced stages of breast cancer [5]. In more recent years, mesenchymal stem cell-derived CCL5 has been shown to contribute to cancer cell motility, invasion and metastasis [49,50]. 4T1 growth characteristics parallel highly invasive human metastatic mammary carcinoma comparable with human stage IV breast cancer [51].…”
Section: Yan Zhang Et Al 405mentioning
confidence: 99%
“…RANTES has been detected in samples from patients with breast cancer, and its expression was correlated with disease progression (23,42,43). Positive feedback between STAT3 and RANTES may increase the aggressiveness of TRM-7 cells.…”
Section: Rantes and Stat3 Blockade Inhibits Drug Resistance In Trm-7mentioning
confidence: 99%
“…(4) MSC hatása a tumor áttétképzésére: Az emlő karcinóma sejtekből felszabaduló osteopontin hatására az MSC-k a CCL5 (RANTES) kemokint termelik [63], mely fokozza a tumor sejtek migrációját, invazivitását és ezáltal áttétek képzését [62]. A csontvelői MSC-k, ill. a tumor mikrokörnyezetében lévő TAF-ok SDF-1 (CXCL12) -et termelnek, ez a sztróma eredetű faktor a tumor sejtek felszínén lévő CXCR4 receptorhoz kötődik, elősegíti a tumor sejtek szóródását, túlélését, a csontvelőbe lépését és az endotél sejtek aktiválása által a daganat neo-angiogenezisét [64,73,74].…”
Section: A Mesenchymalis őSsejtek áLtalános Jellemzéseunclassified
“…Az MSC-k fiziológiás körülmények között a csontvelőben zajló hematopoézis megfelelő környezetének biztosítása mellett részt vesznek a szöveti megújulás és regeneráció folyamataiban [12]. Rákban, mint egy sebgyógyulást mimikáló [154] hozzájárulnak a tumorok immunprivilégiumához [19][20][21][22][23][24][25], valamint a tumor sejtek áttét képzésének fokozásával [62,63]. A Gal-1 fehérje mindhárom fenti folyamat mechanizmusában szerepet játszhat, sőt a Gal-1 termelődés hipoxiás körülmények között szintén a HIF-1 által szabályozott [127].…”
Section: Diszkusszióunclassified
See 1 more Smart Citation